PENGARUH PEMBATASAN PAKAN DENGAN PEMUASAAN DARI UMUR DUA SAMPAI TUJUH MINGGU TERHADAP SENSORIS DAN KANDUNGAN KIMIA DAGING ITIK TURI JANTAN - , MUHAMMAD WILDAN ADI NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study was conducted to evaluate the effect of skip a day and skip two days feeding on performance of male Turi duck age 2 to 7 weeks. A total seventy five male Turi ducks two week of age were randomly assigned into 5 treatments P0, P1-25, P2-25, P1-27 and P2-27. The treatment of P0 was fed ad libittum, P1-25 was skip-a-day feeding every week for 2 until 5 week, P2-25 was skip-two-days feeding every week for 2 until 5 week, P1-27 was skip-a-day feeding every week for 2 until 7 week, P2-27 was skip-two-days feeding every week for 2 until 7 week. The 5 duck groups fed the treatment diets which was formulated with nutrient requirement of National Research Council recommendation and water consumption ad libitum until 7 week. The data collected were lipid composition, dry matter composition, protein composition, ash composition and sensory of Turiâs meat. Data were analyzed by analysis of variance followed by contrast orthogonal and data sensory analyzed by non parametric statistik kruskal walls.The result showed that skip feeding had a significant effect on lipid composition (P<0,05), but not on dry matter, protein composition and sensory of Turiâs meat (P>0,05). it can be concludId that skip-a-day feeding can be better performance on male Turi duck. The best performance obtained on P2-25 (skip-two-days feeding every week for 2 until 5 week).